Persona And Shadow Archetypes Of Achilles In “The Song Of Achilles” - Annisa, Fahira Rasya; Indriani, Ketut Santi; Mulyana, Novita (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study investigates Achilles' psychological depth in Madeline Miller's “The Song of Achilles”, focusing on the role of the Persona and Shadow archetypes in his internal conflict and tragic fate. Using Carl Jung's archetype theory, this study aimed to see how Achilles' Persona is shaped by societal expectations and his mother's desire for him to attain god-like status. In contrast, his Shadow contains his suppressed fears, vulnerability, and emotional attachments, particularly his strong feelings for Patroclus. The conflict between these two opposing forces causes Achilles' emotional isolation and destructive behavior, particularly after Patroclus' death. This conflict, which stems from his failure to adjust to his Persona and Shadow, eventually leads to his downfall. This study emphasizes the importance of archetypal theory in understanding Achilles' character development.